Balas de carmín - García Francés, Alfredo, 1949- (Bogotá, Colombia : Editorial Oveja Negra : Quintero Editores, 2007)
When Lany, the daughter of a prosperous Colombian family, is kidnapped and remains in captivity, she becomes a member of a violent drug gang and a lover of women who cannot escape the consequences of her past no matter where she goes.
Online resource; title from ePub and PDF title page (Digitalia, viewed November 5, 2014)
Keywords: Electronic books